Taking advantage of development opportunities offered by Chinas aid entry in Africa’s market as balancing the act to Western aid - Okoth, George O.; Tonui, Warkach K. (International Journal of Education and Research, 2013)
There is rich evidence that foreign assistance in the development of economies of Africa is widespread. Africa receives a greater share, at 36%, of total global aid to than any other part of the world. Over the past four decades, aid to Africa has quadrupled from around US$11 billion to US$44 billion, with a net increase of almost US$10 billion during the period 2005-2008 alone. However, the debate on how aid can be effective in Africa’s development is, still ongoing without any clear way forward. There is a high volume of literature on the impact of foreign aid on development in Africa, yet not many of them recognize the importance and contributions of China in terms of Aid and development in Africa. A lot of publicity has focused on Western Aid in the development of African economies. This paper recommends that Africa should take advantage of the development opportunities offered by Chinas entry into Africa’s economic space and shun the raging negative debate on her irrelevance in terms of democratic growth. China’s role in Africa is dynamic, with deep historical roots and a wide range of ever-changing engagements and models that do not lend themselves to black-and-white categorization.
Keywords: Development Opportunity; Balancing; China; Western; Aid; Entry; Africa’s Market